Analisis kesulitan kognitif dan masalah afektif siswa SMA dalam belajar matematika menghadapi ujian nasional - Azis Azis; Sugiman Sugiman (Jurnal Riset Pendidikan Matematika, 2015)
Penelitian untuk mendeskripsikan tingkat dan letak kesulitan belajar matematika siswa pada aspek kognitif dan kategorisasi masalah belajar matematika siswa pada aspek afektif dalam menghadapi Ujian Nasional tahun pelajaran 2013/2014 SMA di Kota Baubau. Penelitian ini menggunakan penelitian dengan metode survei. Pengumpulan data yang digunakan adalah teknik pengukuran (tes diagnostik), kuisioner, dan wawancara. Hasil penelitian menunjukkan bahwa tingkat kesulitan belajar matematika yang dialami oleh siswa untuk menyelesaikan soal-soal Ujian Nasional berada pada kategori sedang; letak kesulitan belajar matematika siswa pada aspek kognitif dalam menyelesaikan soal-soal Ujian Nasional dilihat dari segi pengetahuan faktual dengan persentase interval kesulitan sebesar, segi pengetahuan konseptual dengan persentase interval kesulitan sebesar, dan segi pengetahuan prosedural dengan persentase interval kesulitan sebesar; dan kategorisasi masalah belajar matematika siswa pada kategori aspek afektif dalam menghadapi Ujian Nasional tahun pelajaran 2013/2014 SMA di Kota Baubau secara umum berada pada kategori rendah.Kata kunci: kesulitan belajar matematika, kognitif, afektif, ujian nasional SMA An Analysis of Difficulty on Cognitive and Problem on Affective of SMA Students in Mathematics Learning Facing National ExaminationAbstractThis study aims to describe the degree of student’s learning difficulty of mathematics on cognitive and categorization of student’s learning problem on affective aspect in accomplishing mathematic items in facing national final exam of SMA Baubau municipality in 2013/2014 academic year. The research type uses survey method. The technique of data collecting made use of diagnostic test that is National final exam items in 2012/2013 academic year which was modified by the researcher, questionnaires, and interviews. The research result indicates that the degree of students’ learning difficulty of mathematics to accomplish national final exam items is in the medium category; the students’ learning difficulty of mathematics on cognitive aspect in accomplish national final exam items viewed from factual knowledge  with students’ difficulty  interval percentage , conceptual knowledge aspect with students’ difficulty interval percentage , and procedural knowledge aspect with students’ difficulty interval percentage ; and the categorization of students’ learning problem of mathematics on affective aspect in facing National final exam in 2013/2014 academic year of SMA Baubau municipality generally is in the low category.Keywords: Learning difficulty of mathematics, cognitive, affective, SMA National final exam